PENGARUH IMPLEMENTASI AUDIT BERBASIS INTERNASIONAL STANDARDS ON AUDITING TERHADAP KUALITAS AUDITING (Universitas Islam Malang, 2020)
ABSTRACT This study aims to determine the effect of implementation of international-based auditing Standards on auditing on the quality of auditing. The population in this study was Malang City Public Accounting Firm. The sample used was 65 respondents. Data collection methods used questionnaire method and questionnaires were conducted at Malang Public Accountants Office. Data analysis techniques used in this study are simple linear analysis, and partial test. The results showed that partially international Standards on auditing had a significant effect on the quality of auditing. The contribution of research results can provide input to the Public Accounting Firm in Malang, especially auditors in carrying out accounting checks that must be based on General Applicable Accounting Principles and always uphold the accountant's code of ethics as a public accounting profession. Keywords: International Standards on Auditing, Auditing Quality and accountant's code of ethics